Lentigo Senilis (Solar Lentigo): Tinjauan Naratif tentang Epidemiologi, Patogenesis, Gambaran Klinis, Diagnosis, dan Penatalaksanaan - Erika Agustianti; Luluk Hermawati; Nur Bebi Ulfah Irawati; Ratu Nadia; Firda Asma’ul Husna; Hilizza Awalina Zulfa (Universitas Sultan Ageng Tirtayasa, 2026)
Lentigo senilis, also known as solar lentigo, is a common benign hyperpigmented lesion that is closely associated with chronic ultraviolet (UV) exposure and the skin aging process. Although non-malignant, lentigo senilis represents an important manifestation of photoaging and often causes cosmetic concerns, particularly among older individuals. This review aims to summarize current evidence regarding the epidemiology, pathogenesis, clinical characteristics, diagnostic approaches, and management of lentigo senilis using a thematic narrative review approach. A comprehensive literature search of major electronic databases identified relevant studies published between 2015 and 2025. The findings indicate that the prevalence of lentigo senilis increases significantly after the age of 50 years, particularly in individuals with cumulative sun exposure and lighter skin phototypes. The pathogenesis involves UV-induced melanocyte activation, dysregulation of melanogenesis signaling pathways, oxidative stress, and age-related decline in epidermal repair capacity. Clinically, lentigo senilis presents as flat, well-demarcated hyperpigmented macules on sun-exposed areas of the skin. Diagnosis is primarily established through clinical examination and dermoscopy to exclude malignant lesions with similar appearances. Management options include topical depigmenting agents, chemical peels, cryotherapy, laser-based therapies, and intense pulsed light, tailored to lesion characteristics and patient preferences. Preventive strategies emphasizing sun protection remain essential in reducing the incidence and progression of lentigo senilis.